South African International Relations (Ir) and the China-Africa relationship: a critical reflection - Walker, Timothy Charles (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
South African International Relations (IR) is a prominent source of China-Africa research and analysis, producing reports, journal articles and books that seek to illuminate the emerging relationship between China and Africa. It plays an important role in the framing of the relationship, as well as how it is perceived outside of the discipline. However, critical concerns have been raised about the context within which South African IR operates. It is therefore important that IR research, including its assumptions, dominant concepts, professed values and aspirations to studying the China-Africa relationship, be critically examined. The aim of this thesis is to contribute to critical thinking in South African IR by opening up for future discussion the new directions and possibilities for China-Africa IR. Utilising a critique located in Critical International Relations Theory (CIRT), this thesis critically reflects upon both the context of South African IR's China-Africa research and the perspectives it has produced. The thesis argues that in spite of many descriptive and empirical studies, China- Africa research is theoretically underdeveloped in South African IR. Further, it argues that theoretical work is marginalised despite the fact that both historical and contemporary research relies on concepts drawn from IR theory. South African IR's focus on policy relevance is advanced as a reason for the prevalence of theoretical underdevelopment. This thesis concludes by reviewing arguments for the improved use of IR theory in China-Africa IR, which will lead to a better understanding of this important relationship.
Keywords: South Africa -- Relations -- China; China -- Relations -- South Africa; International relations -- Philosophy; Critical theory